1996
DOI: 10.1007/s004310050504
|View full text |Cite
|
Sign up to set email alerts
|

Growth curves in untreated Ullrich-Turner syndrome: French reference standards 1-22 years

Abstract: Reference curves for untreated Ullrich-Turner syndrome are provided, which should form a basis for assessing the impact of growth-promoting treatment in this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Although our growth data generally are consistent with those, some important differences exist. Whereas the Northern Europeans and others have concluded that girls with TS are born quite small (–1.0 to –1.4 SD below the mean) [6, 10, 16, 22, 23, 24], our data suggest that the growth retardation at birth is relatively mild (–0.68 SD). A portion of the difference can be explained by our exclusion of premature infants (gestational age ≤37 weeks).…”
Section: Discussioncontrasting
confidence: 92%
“…Although our growth data generally are consistent with those, some important differences exist. Whereas the Northern Europeans and others have concluded that girls with TS are born quite small (–1.0 to –1.4 SD below the mean) [6, 10, 16, 22, 23, 24], our data suggest that the growth retardation at birth is relatively mild (–0.68 SD). A portion of the difference can be explained by our exclusion of premature infants (gestational age ≤37 weeks).…”
Section: Discussioncontrasting
confidence: 92%
“…Growth patterns of girls with TS are different from those in normal populations mainly because of the short stature homeobox‐containing gene on the X chromosome (SHOX) haploinsufficiency and their ovarian insufficiency. TS‐specific growth curves have been published in various countries 4–11 including Japan, 12 and they have been clinically used for the evaluation of stature and growth. Those of the Japanese were constructed with data from subjects whose body measurements were obtained by sending questionnaires to their follow‐up hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Standing heights were converted into SDS, according to the French population standards for age and gender [25]. Growth retardation was defined as a standing height equal or below -2 SDS for age and gender.…”
Section: Methodsmentioning
confidence: 99%